Explaining Unfavorable Attitudes Toward Religious Out-Groups Among Three Major Religions - Eylem Kanol (Journal for the Scientific Study of Religion, 2021)
Considering intensifying sectarian conflicts in recent years and increasing interreligious violence around the globe, there is a need to further our understanding of negative attitudes toward religious out-groups. To investigate the driving factors behind these negative attitudes among members of the three major Abrahamic religions, I employ original data derived from a survey fielded among 10,046 respondents in eight countries (Cyprus, Germany, Israel, Kenya, Lebanon, Palestine, Turkey, and the USA). A rich body of literature documents the relationship between religious fundamentalism and prejudice. Other scholars have investigated out-group hostility using an intergroup relations perspective, focusing on contact theory, and more recently, on discrimination. While controlling for other relevant factors such as demographic and socioeconomic variables, I investigate the role of religiosity and intergroup relations in explaining unfavorable interreligious attitudes. The results suggest that unfavorable attitudes toward religious out-groups are most strongly associated with religious fundamentalism. This finding is robust across religious groups.
doi:10.7802/2259
Keywords: 300; fundamentalism; out-group hostility; Islam; Christianity; Judaism; attitudes